Statement by the Managing Director on the Independent Evaluation Office Report on IMF Response to the Financial and Economic Crisis : An IEO Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
The Independent Evaluation Office (IEO) has produced a detailed report that provides valuable insights on how the IMF responded to the global financial and economic crisis. The analysis in the report is broadly balanced, and Managing Director welcomes the IEO's finding that the IMF played an important role in the global response to the crisis, and broadly supports the report's recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economic Crisis; Fiscal Policy; Monetary Policy; Policy Advice; PP